2019
DOI: 10.22270/jddt.v9i2.2549
|View full text |Cite
|
Sign up to set email alerts
|

Design of transdermal patch of ketoprofen by full factorial design for treatment of rheumatoid arthritis

Abstract: Oral therapy of NSAIDs for treatment of rheumatoid arthritis causes gastric irritation and ulceration. In the present study transdermal patch of ketoprofen was developed using hydroxyl propyl methyl cellulose E5 and Eudragit S100. Patches were prepared by solvent evaporation method. Optimization was carried out by 32 factorial design with polymer concentration (HPMC E5) and plasticizer concentration (propylene glycol) as independent variables. Patches were evaluated for folding endurance, surface pH, drug cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…Rao et al have prepared a transdermal patch of ketoprofen and its optimization was done using 32 factorial design method, which is in accordance with our proceeding [ 38 ]. In the present study, 32 factorial design was used to evaluate the effect of independent variables (T50% and T80%) of film (dependent variable).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rao et al have prepared a transdermal patch of ketoprofen and its optimization was done using 32 factorial design method, which is in accordance with our proceeding [ 38 ]. In the present study, 32 factorial design was used to evaluate the effect of independent variables (T50% and T80%) of film (dependent variable).…”
Section: Resultsmentioning
confidence: 99%
“…Rao et al have prepared a transdermal patch of ketoprofen and its optimization was done using 32 factorial design method, which is in accordance with our proceeding [38].…”
Section: Factorial Designmentioning
confidence: 99%
“…8 and 9. XRD diffractograms revealed that pure gliclazide showed distinctive peaks in 2θ=14., 17.3, 20.1, 25.8 and 28.4 which indicate the crystalline nature of pure Gliclazide [22]. The XRD patterns of pure drug, polymers, and physical mixture of drug and polymers are represented in Figs.…”
Section: X-ray Powder Diffractometrymentioning
confidence: 97%
“…The length of each strip is measured and variation in length is measured by determining percent constriction. 0% constriction is equivalent to 100% flatness [22].…”
Section: Flatnessmentioning
confidence: 99%
“…The frictional forces in a loose powder can be measured by the angle of repose. It is defined as the maximum angle possible between the surface of the pile of powder and the horizontal plane [26].…”
Section: Evaluation Of Pre-compression Parametersmentioning
confidence: 99%